Two new synonyms among Chinese Thripinae (Thysanoptera: Thripidae) - Mirab-Balou, Majid; Tong, Xiao-Li (Zootaxa, 2015)
Two species of Thripinae described from China, Danothrips dianellae Zhang and Tong, and Taeniothrips calopgomi Zhang, are here recognized as synonyms of two widespread Southeast Asian species.